The Psychological Impact of Live Broadcasting On Mental Health: A Comparative Study of Radio And Television Presenters - Nwoke , Linda, Ifeanyi (International Journal of Scientific Research and Management (IJSRM), 2016)
Live broadcasting is a high-pressure profession that demands optimal performance under intense scrutiny. This exploratory study investigates the psychological impact of live broadcasting on mental health, focusing on pre- and post-broadcast anxiety. A mixed-methods approach combining survey data (n = 100) and in-depth interviews (n = 20) was used with broadcast professionals. Seventy-five percent of participants reported increased anxiety levels before live broadcasts, with peak anxiety occurring 30 minutes prior to broadcast. Post-broadcast anxiety persisted in 40% of participants, with symptoms lasting up to two hours. Multivariate analysis revealed significant predictors of pre-broadcast anxiety: experience (β = -0.23, p < 0.01), self-efficacy (β = -0.31, p < 0.001), and social support (β = -0.25, p < 0.01). This study highlights the significant psychological impact of live broadcasting on mental health, underscoring the need for targeted interventions. By understanding the predictors of pre- and post-broadcast anxiety, broadcasters and mental health professionals can develop evidence-based strategies to mitigate these effects, thereby enhancing well-being and performance in high-pressure broadcasting environments. Specifically, the findings have important implications for informing evidence-based guidelines for broadcast professionals' mental health support, developing anxiety-reduction interventions tailored to live broadcasting contexts, and enhancing broadcast engineering design to incorporate mental health considerations.